Indirect calorimetry to estimate energy requirements for growing and finishing Nellore bulls (2017)
ABSTRACT: Determination of nutritional requirements is the basis for diet formulation. The objectives of this study were to determine the net energy requirements for maintenance (NEm) and weight gain (NEg) in Nellore bulls during the growing and finishing phases, and to estimate efficiency of metabolizable energy (ME) utilization for maintenance and gain (km, kg). Five Nellore bulls were housed in individual pens at the Universidade Federal de Minas Gerais (Belo Horizonte, Brazil) and evaluated over four experimental periods at 210, 315, 378 and 454 kg shrunk body weight (SBW), approximately. During each period, heat production (HP) was quantified by open circuit indirect calorimetry for three feeding levels: ad libitum, restricted and fasting. The NEm requirement was determined by linear regression between the Log of HP and the ME intake (MEI) for the ad libitum and restricted levels. This requirement was also determined by quantifying fasting heat production (FHP). The NEg requirement was calculated by the difference between MEI and HP during ad libitum feeding. The km and kg were calculated by the relationship between net energy (NE) and ME requirements for maintenance and weight gain (MEm, MEp), respectively. The NEm requirements per kg of metabolic empty body weight (EBW0.75) fluctuated between 348 and 517 kJ d−1, showing a decreasing trend with age, and were higher than the values reported in the literature. The NEg requirements ranged between 48.3 and 164 kJ kg−1 EBW0.75 d−1, and varied according to age and weight gain. The km values varied between 58.6 and 69.7%, while kg varied between 23.4 and 40.2%. We concluded that NEm and NEg requirements were influenced by age and possibly by the level of stress, nervousness and activity of animals into the respirometry chamber. Further studies should quantify HP with records of positional changes (time spent standing vs. lying down). Additionally, HP quantification should be repeatedly performed in the same experimental period to obtain a representative value of NEg requirements.